Business decision preference - qualitative study on SMES owner in the post pandemic era - Satrio Matin Utomo (Universitas Islam Lamongan, 2022)
Pandemic has hit the business world. All business entities, especially the SMES had to deal with the negative impacts of the pandemic. They should stop – simply because the business could not compete in the market anymore. However, things have gone better, and so would the business world. This paper investigate the business decision preference among a number of SMES of a small local organization in West Jakarta, Indonesia. The findings stated that although the business owners would like to restart their business, there were severals factors that have been their concerns. Those factors are; the uncertainty of the conditions, the fear of failure, and the “starting over and search for new buyers